2010
DOI: 10.1111/j.1464-5491.2010.02957.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glycaemic control on platelet bound CD40–CD40L system, P‐selectin and soluble CD40 ligand in Type 2 diabetes

Abstract: Type 2 diabetes is associated with up-regulation of the platelet-bound CD40-CD40L system, platelet hyperactivity (enhanced P-selectin expression) and increased sCD40L levels. Improved glycaemic control, however, does help to correct abnormal platelet activation via down-regulation of CD40-CD40L system and P-selectin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Other researchers reported similar findings in a subsequent study in Europeans with T2D. 28 Interestingly, this latter publication also reported a significant decrease in platelet TNFR5 signalling following sustained reduction in haemoglobin A1C, indicating that the process may be reversible. A positive correlation between glycaemic control and sCD40L level has also recently been reported in patients with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 66%
“…Other researchers reported similar findings in a subsequent study in Europeans with T2D. 28 Interestingly, this latter publication also reported a significant decrease in platelet TNFR5 signalling following sustained reduction in haemoglobin A1C, indicating that the process may be reversible. A positive correlation between glycaemic control and sCD40L level has also recently been reported in patients with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 66%
“…This has previously been observed in adults with T2D (9,10), in whom improved glycemic control correlated with a decline in measured platelet activation markers, suggesting that platelet hyperactivity can be reversed with improved metabolic control (9,10). The size of the current study did not allow for a comparison of subjects prescribed insulin with those who were not.…”
Section: Discussionmentioning
confidence: 61%
“…In the studies, where the acute coronary patients were enrolled, sCD40L was found as a marker of inflammatory thrombotic activity and found related with further increased cardiovascular events [21, 22]. Recently, CD40/CD40L pathway activation and a subsequent proinflamatory milieu were reported in diseases such as obesity [24, 25], diabetes mellitus [26] and hypertension [27]. Whether migraine patients constitute a low- or high-risk group for cardiovascular disease is obscure, but high-sCD40L levels in migraine patients in our study support the presence of a vascular damage in migraine.…”
Section: Discussionmentioning
confidence: 99%